Antioxidant and antimicrobial activities of nanosilver-mycomeat composite produced through solid state fermentation of tigernut waste and cassava pulp by Pleurotus pulmonarius - Bamigboye, C O; Amao, J A; Fadiora, I A; Adegboye, J D; Akinola, O E; Alarape, A A; Oyeleke, O R; Adebayo, E A (IOP conference series. Materials Science and Engineering, 2020)
Bacterial deterioration is one of the most critical subjects in the production, processing, transport, and storing of food. The search for novel materials for the synthesis of nanoparticles is unending and this is likely to continue in the upcoming years. In this study, mycomeat samples were produced using cassava pulp (C) and tiger nut aggregate waste (T). The mycomeat extracts were used to produce nanosilver-mycomeat by catalytic conversion of Ag+ to Ag0. The antioxidant and antimicrobial activities of the nanosilver-mycomeat composites were determined using established methods. The nanosilver-mycomeat composites of both C and T showed increased antioxidant and antimicrobial activities compared to the ordinary mycomeat extract. This can find applications in the packaging of food, thereby preventing food samples from deterioration.